2017
DOI: 10.1002/hed.25018
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of endovascular embolization or stent‐graft reconstruction for treatment of acute carotid blowout syndrome in patients with head and neck cancer: Case series and systematic review of observational studies

Abstract: Both embolization and stent grafts are safe therapeutic options for acute carotid blowout syndrome. Embolization for ICA/CCA carotid blowout syndrome was associated with higher risks of procedural stroke and lower recurrent bleeding compared to stent grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…However, 8%-14% of patients can incur a permanent ischemic insult from embolization of the affected artery [4]. In 2018, a study by Wong et al found that out of 266 patients, there was a 10.3% complication rate of ischemic events after embolization of the CCA or ICA and a 2.5% complication rate after stent reconstruction [5]. Rebleeding occurred in 31.9% of those treated with stents and in 9.1% of those with therapeutic endovascular occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 8%-14% of patients can incur a permanent ischemic insult from embolization of the affected artery [4]. In 2018, a study by Wong et al found that out of 266 patients, there was a 10.3% complication rate of ischemic events after embolization of the CCA or ICA and a 2.5% complication rate after stent reconstruction [5]. Rebleeding occurred in 31.9% of those treated with stents and in 9.1% of those with therapeutic endovascular occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, as demonstrated in a large metaanalysis of 559 patients by Bond et al, up to 20% of the patients who passed a BOT had a delayed ischemic event [6]. Endovascular reconstruction of the damaged artery with stents to decrease the risk of neurologic sequela in those who fail a BOT may be feasible, but can result in higher rates of rebleeding and delayed stroke [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Regional metastases in the cervical lymph nodes and locally advanced disease in the pharynx and at the skull base can encase and erode into the great vessels of the neck. The internal jugular vein will typically collapse and occlude without ill effect, but the carotid artery system, if broached can lead to exsanguinating hemorrhage, the dreaded “carotid blowout.” Endovascular techniques such as embolization or more recently, covered stenting have provided significant temporization of such bleeds . This can have the good result of diverting death to another more acceptable cause (such as hypercalcemia of malignancy).…”
Section: Case: 59 Yof With Sentinel Carotid Hemorrhagementioning
confidence: 99%
“…Tumor encasement of the common carotid artery (CCA) and/or the internal carotid artery (ICA) in patients with advanced head and neck tumors represents a significant surgical challenge. The 5-year survival rate is about 5%-13% 1 partly due to risks of stroke or carotid blowout syndrome (CBS).Previous approaches to the prevention of CBS (e.g., surgical ligation, endovascular embolization, covered stent implantation) were palliative and most reports did not further solve the tumor burden [2][3][4] .Simple surgical management, e.g., peeling the tumor off the carotid wall, resection with ligation of the carotid artery, resection with or without revascularization, results in non R0 resection or intraoperative and postoperative complications, even the difficulty of the operation is a significant challenge for the surgeon 1,[5][6] .Therefore, we report our experience with combination of oncologic complete tumor resection and intravascular covered stent placement in patients with advanced head neck cancer.…”
Section: 、 、 、Introductionmentioning
confidence: 99%